2017
DOI: 10.1016/j.jrurstud.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Understanding private forest owners’ conceptualisation of forest management: Evidence from a survey in seven European countries

Abstract: Private forest owners' involvement in forest management has been frequently examined through the attitudes, values, beliefs, objectives and motivations associated with owning and managing forestland. Owners' views on forest management do not always align with those of policymakers who believe forest owners do not actively manage their forests. However, empirical studies on forest owners' conceptualisations of forest management are scarce. To determine how private forest owners in Europe conceptualise forest ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 66 publications
3
58
2
2
Order By: Relevance
“…For example, the dynamics between instrumental and intrinsic values among forest owners may be different outside Finland. However, also a wider European study highlights the multiple objectives of forest owners; forest owners increasingly manage their forests for multiple objectives such as maintaining ecosystems instead of only exploiting the timber (Feliciano et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the dynamics between instrumental and intrinsic values among forest owners may be different outside Finland. However, also a wider European study highlights the multiple objectives of forest owners; forest owners increasingly manage their forests for multiple objectives such as maintaining ecosystems instead of only exploiting the timber (Feliciano et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Kline et al (2000) also recognised a group of passive owners. Feliciano et al (2017) conducted a survey in seven European countries and found that private forest owners in Western European countries emphasise ecosystem-oriented forest management and the concept of multi-functionality more, while economic aspects and maintaining the good growing condition of forests are more important in Eastern European countries.…”
Section: Forest Owner Researchmentioning
confidence: 99%
“…In parallel, research efforts are increasingly devoted to understand what may reorient NIPF owners' choices towards management objectives inclusive of public FESs. This emerging research has shown that NIPF owners are a multifaceted group with several objectives (Ní Dhubháin et al 2007;Howley 2013;Feliciano et al 2017): some of them prioritise goals related to production of FESs for the market; others prefer goals related to self-consumption of FESs, such as recreation and amenities delivered by their forest estate (Boon et al 2004;Kendra and Hull 2005;Serbruyns and Luyssaert 2006;Butler et al 2007). The research has also highlighted that although financial compensation may help, the delivery of public FESs by NIPF owners goes far beyond a matter of public policy or support while stretching across a wide set of factors, including the ownership characteristics, the owner's personal features and motivations and the socioeconomic context (Harrison et al 2002;Boon et al 2010;Song et al 2014; Rodríguez-Vicente and Marey-Pérez 2010; Domínguez and Shannon 2011).…”
Section: Introductionmentioning
confidence: 99%